Firms' Responses to Anticipated Reductions in Tax Rates: The Tax Reform Act of 1986 - Scholes, Myron S.; Wilson, G. Peter; Wolfson, Mark A. (Journal of Accounting Research, 1992)
Myron S. Scholes, G. Peter Wilson, Mark A. Wolfson, Firms' Responses to Anticipated Reductions in Tax Rates: The Tax Reform Act of 1986, Journal of Accounting Research, Vol. 30, Studies on Accounting and Taxation (1992), pp. 161-185